Effect of moist heat versus cold therapy on leg muscle cramp among patients on hemodialysis: randomized control trial - Mohammed, Dr. Heba Ahmed; El-Deen, Dr. Dalia Salah (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Muscle cramps that occur during hemodialysis can result in shortening of treatment or reduction of fluid removal which may lead to inadequate clearance of waste products, fluid overload which significantly increase mortality risk. Aim of the current study was to investigate the effect of moist heat versus cold therapy on leg muscle cramp among patients on hemodialysis. Design: A randomized control clinical trial design was utilized to accomplish this study purpose. Research hypothesis: H1 &H2: The intervention groups who received either moist heat or cold therapy will have a significant lower mean pain and muscle cramp intensity score compared to the control group who received routine hospital care. H3& H4: There will be a difference between applying moist heat versus cold therapy on mean pain and muscle cramp intensity score among the intervention groups Sample: A sample of 90 adult male and female patients who met the inclusion criteria was invited to share in the research. Results:There were significant reduction in the intensity of pain and muscle cramp in the study groups more than control group. Moreover, moist heat therapy group was more effective than cold therapy to reduce intensity of pain and muscle cramp for patients on hemodialysis. Conclusion: moist heat and cold therapy are effective to  reduce intensity of pain and muscle cramp for patients on hemodialysis . Recommendation: Further studies are required to explicate the effectiveness of heat vs cold therapy on leg muscle cramp among hemodialysis and pretonieal dialysis with large sample size of patients in different health care settings.